2021
DOI: 10.3390/microorganisms9071474
|View full text |Cite
|
Sign up to set email alerts
|

Babesia pisicii n. sp. and Babesia canis Infect European Wild Cats, Felis silvestris, in Romania

Abstract: Haemoparasites of the genus Babesia infect a wide range of domestic and wild animals. Feline babesiosis is considered endemic in South Africa, while data on Babesia spp. infection in felids in Europe is scarce. Using samples from 51 wild felids, 44 Felis silvestris and 7 Lynx lynx, the study aimed to determine the presence and genetic diversity of Babesia spp. in wild felids in Romania by analyzing the 18S rDNA and two mitochondrial markers, cytochrome b (Cytb) and cytochrome c oxidase subunit I (COI) genes. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 63 publications
0
9
0
Order By: Relevance
“…In Europe, epidemiological data on Babesia infection in domestic cats are limited to a few molecular studies targeting the 18S rDNA , with B. canis reported in Spain and Portugal [ 14 , 15 ], B. vogeli in Portugal [ 15 , 16 ], and B. microti in Italy [ 12 , 13 ]. Babesia canis was also recently reported in wild cats from Romania [ 18 ].…”
Section: Discussionmentioning
confidence: 80%
See 4 more Smart Citations
“…In Europe, epidemiological data on Babesia infection in domestic cats are limited to a few molecular studies targeting the 18S rDNA , with B. canis reported in Spain and Portugal [ 14 , 15 ], B. vogeli in Portugal [ 15 , 16 ], and B. microti in Italy [ 12 , 13 ]. Babesia canis was also recently reported in wild cats from Romania [ 18 ].…”
Section: Discussionmentioning
confidence: 80%
“…The 18S rDNA , a highly conserved region, is the primary PCR target used in studies addressing the diagnosis of piroplasmids [ 71 , 72 ]. However, several studies have questioned its ability to differentiate between closely related species [ 2 , 18 , 64 , 73 , 74 ]. In the present study, BLAST analyses of the 18S rDNA sequences showed 99–100% identity with different sequences of B. canis , although the presence of this species was confirmed in only six samples by Cytb gene amplification and analyses.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations